Similarities and differences Between Thesis Supervision and Counselling - Osborne, John O. (Canadian Journal of Counselling and Psychotherapy, 2007)
Thesis supervison can bring to light unresolved and new psychological issues for both supervisors and students. What makes thesis supervision especially difficult is that supervisors have no official mandate to deal with disruptive psychological processes. In fact, there are prohibitions against such interpersonal involvement. Those supervisors who move beyond the borders of traditional, rationally based, problem solving are engaging in a boodeg activity. The similarities and differences between the contexts of thesis supervision and counselling are discussed with a view to highlighting this problem and with particular reference to transference phenomena.